Predictors of upper respiratory tract symptom risk: Differences between elite rugby union and league players - Keany, L. C.; Kilding, A. E.; Merien, F.; Shaw, D. M.; Borotkanics, R. J.; Cupples, B.; Dulson, D. K. (Journal of Sports Sciences, 2021)
This study examined possible predictors of upper respiratory tract symptom (URTS) episodes in elite rugby union and league players (n = 51) during intensive pre-season training. Baseline saliva and blood samples were collected in the first week of pre-season training for analysis of salivary secretory immunoglobulin A (SIgA) and cytomegalovirus. Thereafter, SIgA, URTS, internal training load and self-reported wellness data were repeatedly measured throughout a 10-week pre-season training period. Univariate frailty model analysis, which included 502 observations, was performed for each rugby code for the following independent predictor variables: SIgA concentration, internal training load, total wellness, sleep quantity, sleep quality and stress. Rugby union and league players experienced a similar number of URTS episodes; however, predictors of URTS episodes differed between the codes. No biomarkers or self-reported measures significantly predicted URTS risk in rugby union players, while reductions in self-reported total wellness (HR: 0.731, p = 0.004) and sleep quality (HR: 0.345, p = 0.001) predicted increased URTS risk in rugby league players. The findings from this study highlight that factors influencing URTS risk are perhaps sport specific and this may be attributed to different sporting demands and/or different management of players by team-practitioners.